Enzyme Development and Glyoxysome Characterization in Cotyledons of Cotton Seeds - Bortman, Stephen J. (1981)
Unimbibed, mature cotton seeds (cv. Deltapine 61) were found to possess activity for all gluconeogenesis-related enzymes examined, except for isocitrate lyase activity. This indicates that transcription and translation of most enzymes needed for postgerminative growth takes place during seed maturation. This is in contrast with the generalization that “germination” enzymes are synthesized de novo from previously untranslated mRNAs conserved in dry seeds. All enzyme activities increased 3-fold or greater following imbibition, and most remained constant after reaching their peak. Notable exceptions were activities for three β oxidation enzymes and fructose bisphosphatase, which decreased precipitously after peaking with other enzyme activities. Standard sucrose gradient procedures with swing-out rotors were not useful for isolating cotton glyoxysomes. Satisfactory and reproducible results ultimately were obtained with sucrose gradients constructed in a Beckman JCF-Z zonal rotor. Specific activities of glyoxysomal enzymes were 2- to 3-fold lower than those reported for other oil seeds, except malate dehydrogenase which was 10-fold lower. Electron microscopy revealed that protein body fragments were the primary contaminant of glyoxysome fractions. Glyoxysomes were subfractionated by osmotic shock treatments to evaluate sub-organelle localization of constituent enzymes, several of which have not been examined in other oil seeds.